Closure of the patent ductus arteriosus with a Ligaclip through a minithoracotomy. - Majid, A.A. (1993)
This article describes a technique which allows the patent ductus arteriosus (PDA) to be closed through a minithoracotomy. It combines a simple method of inducing atelectasis with Ligaclip closure of the PDA through a subaxillary incision. It was used successfully in 11 children and adolescents.